A note on an abnormal pectoral fin in Puntius amphibia (Val.) - T. Venkateswarlu (Acta Ichthyologica et Piscatoria, 1972)
This paper deals with an account of an abnormal pectoral fin in Puntius amphibia (Val.), obtained from the river Ganges at Patna (Bihar, India). The specimen possessed two pectoral fins, instead of one, on the left side.